2008
DOI: 10.1007/s11065-008-9061-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Impairment in Systemic Lupus Erythematosus: A Comparison with Multiple Sclerosis

Abstract: In this manuscript, we review literature describing the neuropsychological and brain imaging characteristics of systemic lupus erythematosus (SLE) patients. The findings are compared and contrasted with multiple sclerosis (MS) studies, revealing similarities and differences of interest to clinicians and researchers. While cognitive impairment is somewhat less common in SLE than MS, the diseases share a similar cognitive profile with deficits most prominent on tests emphasizing the speed of information processi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
54
1
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 166 publications
(215 reference statements)
7
54
1
7
Order By: Relevance
“…6,7 Aspects of cognitive functioning most commonly affected in MS patients include processing speed, learning, and memory. [6][7][8][9] Characterization of the relationship between cognitive performance and fatigue is complicated by the subjective experience of patients. 10 While patients often believe that fatigue contributes to poor cognitive performance, most research has not found a consistent association between fatigue and actual cognitive performance.…”
Section: Interventions and Assessmentsmentioning
confidence: 99%
“…6,7 Aspects of cognitive functioning most commonly affected in MS patients include processing speed, learning, and memory. [6][7][8][9] Characterization of the relationship between cognitive performance and fatigue is complicated by the subjective experience of patients. 10 While patients often believe that fatigue contributes to poor cognitive performance, most research has not found a consistent association between fatigue and actual cognitive performance.…”
Section: Interventions and Assessmentsmentioning
confidence: 99%
“…2 Although SLE and MS have notable differences in etiology, there is a marked overlap concerning the CNS inflammatory and neurodegenerative nature of these 2 diseases. 3 In 1972, Fulford et al 4 first coined the term "lupoid sclerosis" when referring to patients with SLE who presented with symptoms similar to those in MS. Additionally, neuropsychological and cognitive testing revealed similarities in cognitive profiles of patients with MS and those with SLE that may be the result of similar dysfunctional CNS structures. 5,6 These neuropsychological findings included deficits in working memory and processing speed and general lower cognitive scores, even in the absence of a diagnosed neurologic or psychiatric condition.…”
mentioning
confidence: 99%
“…However, many previous reports already proved increased frequency of WMH in SLE and NPSLE 21, 2936 . WMH had been shown to involve preferentially the frontal and parietal lobes, consistent with an anterior to posterior gradient, similar to other causes of WMH, but different from inflammatory demyelinating etiologies such as multiple sclerosis 8, 37 . In a quantitative cerebral MRI assessment, Appenzeller et al 34 showed that age, duration of neuropsychiatric manifestations and total corticosteroid dosage were independent predictors for WMH in SLE.…”
Section: Introductionmentioning
confidence: 75%
“…Nonetheless, advanced MRI sequences in NPSLE demonstrated underlying abnormalities in normal appearing white and grey matter, which shows the limitations of conventional sequences 51, 62, 63 . Recent studies used advanced MRI techniques in the analysis of NPSLE, as the assessment of tissue-specific atrophy by morphometric methods 37, 51, 64 , diffusion-tensor imaging 51, 63, 65, 66 , magnetization transfer imaging 51, 65, 66 , magnetic resonance spectroscopy 66, 67 and perfusion MRI.…”
Section: Introductionmentioning
confidence: 99%